The Effect of Tax Aggressiveness and Media Exposure on Corporate Social Responsibility (CSR) Disclosure in Mining Sector Companies Listed on the Indonesia Stock Exchange (IDX) in 2023-2024 - Miya Fadila; Novira Sartika (Majapahit Journal of Islamic Finance and Management, 2025)
This research explores the effects of tax aggressiveness and media exposure on corporate social responsibility (CSR) reporting in IDX-listed mining firms spanning 2023 to 2024. It emphasizes the mining sector's notable social and environmental issues, which call for greater transparency in corporate social responsibility (CSR), particularly for companies pursuing assertive tax tactics or facing heightened public attention. Employing a quantitative framework, the study analyzed secondary data from annual reports and sustainability reports via multiple linear regression using SPSS version 29. The study's outcomes show that tax aggressiveness yields a significant positive impact on corporate social responsibility (CSR), whereas media exposure produces a substantial negative influence. Together, they deliver a meaningful effect on corporate social responsibility (CSR). These results point to the idea that corporate social responsibility (CSR) disclosures in the mining industry are largely strategic, designed to uphold the firm's legitimacy and image.